1,4-Diphenalkylpiperidines: A new scaffold for the design of potent inhibitors of the vesicular monoamine transporter-2 - Nickell, Justin R. (Bioorg Med Chem Lett, 2016)
A series of 1,4-diphenalkylpiperidine analogs were synthesized and evaluated for their affinity and inhibitory potency at the [(3)H]dihydrotetrabenazine (DTBZ) binding site and [(3)H]dopamine (DA) uptake site on the vesicular monoamine transporter-2 (VMAT2). Results revealed that translocation of the phenethyl side chains of lobelane from C2 and C6 to C1 and C4 around the central piperidine ring slightly reduces affinity and inhibitory potency at VMAT2 with respect to lobelane. However, methoxy and flouro-substitution of either phenyl ring of these 1,4-diphenethyl analogs afforded VMAT2 inhibition comparable or higher (5-fold) affinity at the DTBZ binding and DA uptake sites relative to lobelane, whereas replacement of the 4-phenethyl moiety in these analogs with a 4-phenmethyl moiety markedly reduced affinity for the DTBZ binding and DA uptake sites by 3- and 5-fold, respectively. Among the twenty five 1,4-diphenethylpiperidine analogs evaluated, compounds containing a 4-(2-methoxyphenethyl) moiety exhibited the most potent inhibition of DTBZ binding and vesicular DA uptake. From this subgroup, analogs 8h, 8j and 8m exhibited Ki values of 9.3 nM, 13 nM and 13 nM, respectively, for inhibition of [(3)H]DA uptake by VMAT2, and represent some of the most potent inhibitors of VMAT2 function reported thus far.